Frekuensi Antenatal Care Tidak Berhubungan dengan Tingkat Pengetahuan Perawatan Kesehatan pada Ibu Nifas - Fatimatasari Fatimatasari; Ashon Sa’adi; Widati Fatmaningrum (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Maternal health care knowledge affects prenatal care and pregnanci’s outcome. Antenatal care is one opportunity to increase maternal health care knowledge. This study aims to investigate the association between antenatal care visits and level of maternal health knowledge among postpartum women in RSUD Majenang. This study was a cross sectional design. The sample was thirty five Postpartum women who admitted in RSUD Majenang on 12th May to 12th June with criteria: being on post partum period, had aterm pregnancy, could show KIA books, had maximally senior high school graduated and performed antenatal care with obstetric and gynecologist maximally twice during pregnancy. Antenatal care visits assessed by questionnaire and antenatal visits record in KIA book. Level of maternal health care knowledge was assessed by questionnaire and interview. This study found 62.9% of total respondents had good antenatal care visits, 28.6% moderate and 8.6% had less antenatal care visits during last pregnancy. 57.1% of total respondents had moderate maternal health care knowledge, 31.4% less and 11.4% had good maternal healthcare knowledge. Spearman Rank test with the significance level  = 0.05 showed p value = 0, 293, it means there is no significant association between antenatal care visits and level of maternal health care knowledge. Conclusion, the un significant association between antenatal care visits level of maternal health care knowledge among postpartum women in RSUD Majenang may caused by many factors, such as the respondents belief about maternal health care information, diverse information resources, insufficient education materials from health care providers and lack of anteatal care quality assessment from health ministry.